2022
DOI: 10.1097/wnr.0000000000001853
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine inhibits high glucose-induced endoplasmic reticulum stress in HT22 cells by upregulation of growth differentiation factor 11

Abstract: Hyperglycemia-induced neuronal endoplasmic reticulum (ER) stress is particularly important for the pathogenesis of diabetic encephalopathy. Spermidine (Spd) has neuroprotection in several nervous system diseases. Our current study to explore the potential protective role of Spd in hyperglycemia-induced neuronal ER stress and the underlying mechanisms. HT22 cells were treated with high glucose (HG) to establish an in-vitro model of hyperglycemia toxicity. The HT22 cells' activity was tested by cell counting kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Modulation of GDF11 serves as an attractive marker for HCC prediction, prevention and novel therapy. Notably, it has been verified that spermidine can inhibit high glucose-induced endoplasmic reticulum stress in HT22 cells via the upregulation of GDF11, and can prevent liver fibrosis and HCC by activating MAP1S-mediated autophagy (36,37). These previous findings indicated that spermidine may be developed as a suitable drug candidate for the induction of GDF11 in HCC treatment.…”
Section: Discussionmentioning
confidence: 85%
“…Modulation of GDF11 serves as an attractive marker for HCC prediction, prevention and novel therapy. Notably, it has been verified that spermidine can inhibit high glucose-induced endoplasmic reticulum stress in HT22 cells via the upregulation of GDF11, and can prevent liver fibrosis and HCC by activating MAP1S-mediated autophagy (36,37). These previous findings indicated that spermidine may be developed as a suitable drug candidate for the induction of GDF11 in HCC treatment.…”
Section: Discussionmentioning
confidence: 85%